A REVIEW ON SYNTHESIS OF CONDUCTING WITH POLYANILINE RICE HUSK ASH SILICA NANOCOMPOSITES AND APPLICATION - Oudah Mezan, Salim; Mohammed Hello, Kasim; Hasan Jabbar, Abdullah; Qabel Hamzah, Maytham; Tuama, AlaaNihad; M., S.Roslan; Arif Agam, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Nanostructures have a prominent place in nanotechnology since more space can be used in different applications. In the past decades, a class of conductive polymers became famous because of their mechanical and electrical properties. Polyaniline is a conductive polymer popularly known as an environmentally stable and highly adjustable polymer given in an application form of powder, membranes, or loose fibers. Low-cost polyolefin and large-scale production are widely used in broad applications. Rice Husk Ash (RHA) is the byproduct of the rice mill industry, considered as waste material. Many types of research focused on RHA targets the high silicate content to be converted to silica after rice husk (RH) pyrolysis undertaken in a furnace with the temperature at 800°C. The sol-gel technique offered a simple route in producing silica from RHA, where 3-(chloropropyl)triethoxysilane (CPTES) is used to convert the RHA into high-quality silica. Polyaniline/Rice Husk Ash Silica Nanocomposites (PANI/RHACCl (SiO₂)NCs) are prepared via chemical oxidative polymerization and can be used in various applications such as supercapacitors, pseudocapacitors, coatings, metal absorption, chemicals, encapsulation of light-emitting organs, proton exchange membranes, diffusion membranes, devices, sensors, and flexible nanoelectronic devices, as well as drug delivery.